Do Orientation-Based Differences in Nestbox Temperature Cause Differential Ectoparasite Load and Explain Patterns of Nest-Site Selection and Offspring Condition in Great Tits?. (24th November 2011) - Goodenough, Anne E.; Elliot, Simon L.; Hart, Adam G.
Abstract : Nest ectoparasites have been linked previously to patterns of nest-site choice and breeding success in birds. Recent research has shown nestboxes facing south-southwest are occupied less frequently by great tits ( Parus major ) than identical boxes facing other directions, and are associated with reduced offspring condition. Here, we investigate the hypothesis that these findings are due to ectoparasite load being directionally nonuniform, possibly because of nonuniformity in nestbox internal temperature. Nests contained, in order of prevalence, hen fleas ( Ceratophyllus gallinae ), haematophagous blowflies ( Protocalliphora spp.), biting lice (Ischnocera), and ticks/mites (Acari). Although southwest-facing nestboxes were significantly warmer than other boxes, there was no directional difference in total ectoparasite load or abundance of particular species. Similarly, there was no relationship between abundance of any ectoparasite species (either per-nest or per-chick) and avian offspring condition determined using wing length or relative mass. We discuss several possible, nonmutually exclusive, explanations for this, including compensatory responses, costs of parasitism being transferred to parents, and condition-dependent effects.